Incentive pricing and cost recovery at the basin scale - Ward, Frank A.; Pulido-Velazquez, Manuel (Journal of environmental management, 2009)
Incentive pricing programs have potential to promote economically efficient water use patterns and provide a revenue source to compensate for environmental damages. However, incentive pricing may impose disproportionate costs and aggravate poverty where high prices are levied for basic human needs. This paper presents an analysis of a two-tiered water pricing system that sets a low price for subsistence needs, while charging a price equal to marginal cost, including environmental cost, for discretionary uses. This pricing arrangement can promote efficient and sustainable water use patterns, goals set by the European Water Framework Directive, while meeting subsistence needs of poor households. Using data from the Rio Grande Basin of North America, a dynamic nonlinear program, maximizes the basin's total net economic and environmental benefits subject to several hydrological and institutional constraints. Supply costs, environmental costs, and resource costs are integrated in a model of a river basin's hydrology, economics, and institutions. Three programs are compared: (1) Law of the River, in which water allocations and prices are determined by rules governing water transfers; (2) marginal cost pricing, in which households pay the full marginal cost of supplying treated water; (3) two-tiered pricing, in which households' subsistence water needs are priced cheaply, while discretionary uses are priced at efficient levels. Compared to the Law of the River and marginal cost pricing, two-tiered pricing performs well for efficiency and adequately for sustainability and equity. Findings provide a general framework for formulating water pricing programs that promote economically and environmentally efficient water use programs while also addressing other policy goals.